Language education at the University of Aveiro before and after Bologna: practices and discourses - Pinto, Susana (2013)
Higher education plays a fundamental role in the construction of a European citizenship that demands the development of plurilingual competences. Although the Bologna Process highlights that development (relating it to mobility, employability and lifelong learning), language education does not seem to be a priority in the agenda of higher education institutions (Tudor 2006).In the context of curricular restructuring required by the Bologna Process, this article presents a case study of the University of Aveiro (UA), Portugal, which set out to describe institutional practices and discourses concerning the use and function of languages in undergraduate and postgraduate education in two academic years (2002–2003 and 2007–2008, before and after the restructuring). In order to identify practices, we analysed the programmes of all language courses.This allowed us to identify the languages and language courses offered, as well as the degree programmes into which they are integrated. In order to access institutional discourses, we interviewed seven actors responsible for training and management at the UA (Rectors, Vice-Rectors, the Head of the Department of Languages and Cultures, The Erasmus Programme Coordinator, and the President of the Students’ Union). The results show that the Bologna Process has had a limiting effect on language education: fewer language courses are offered and fewer degree programmes include them. This converges with the institutional actors’ discourses, since they do not recognize the institution’s responsibility to develop students’ plurilingual competences and tend to value only the instrumental role of English.